DETERMINAN PEMBIAYAAN BERMASALAH PADA BANK SYARIAH DI INDONESIA - Destiana, Rina (Program Studi Akuntansi, Universitas Kuningan, 2018)
This study aimed to examine and analyze the influence of liquidity, efficiency, capital and inflation on non-performing financing at sharia banks in Indonesia. The research data is secondary data obtained from the Financial Services Authority and Bank Indonesia. The data were analyzed using multiple linear regression analysis. Before the data is analyzed further, classical assumption test is done which include normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. Based on the hypothesis test using t test, it is concluded that only the capital has an effect on the problem financing, while the liquidity, efficiency and inflation do not affect the problematic financing of syariah bank in Indonesia. Keywords: efficiency, inflation, liquidity, capital, problem financing